2017
DOI: 10.4194/1303-2712-v17_3_16
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Production of YY-males is one of the most important alternatives to the commercial use of hormones for producing monosex populations in the culture of Nile tilapia. One of the final stages of YY-technology is the feminization of the progeny of XY-females in order to obtain YY-females, which when crossed with YY-males makes possible to obtain populations composed of 100% YY-males. The aim of the study was to evaluate the effects of four concentrations (100, 200, 300, 400 mg kg -1 ) of estrogen 17α-ethinylestrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Thus, it is possible that diets supplemented with E 2 increase the circulating levels of this hormone in the treated fish, promoting the gonadal differentiation during the initial development of this species. In fact, this has been seen in several studies (Marín-Ramírez et al, 2016;Juárez-Juárez et al, 2017;Alcántar-Vázquez, 2018;Vidal-López et al, 2019) in which diets supplemented with E 2 promote fish gonadal differentiation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, it is possible that diets supplemented with E 2 increase the circulating levels of this hormone in the treated fish, promoting the gonadal differentiation during the initial development of this species. In fact, this has been seen in several studies (Marín-Ramírez et al, 2016;Juárez-Juárez et al, 2017;Alcántar-Vázquez, 2018;Vidal-López et al, 2019) in which diets supplemented with E 2 promote fish gonadal differentiation.…”
Section: Discussionmentioning
confidence: 76%
“…It has been previously shown that the sexual differentiation in fish is regulated by sex steroid hormones (Singh, 2013;Pradhan and Olsson, 2015;Hoga et al, 2018) and indirectly by steroidogenic enzymes (Baroiller and D'Cotta, 2001;Tokarz et al, 2015;Di Rosa et al, 2016;Koyama et al, 2019). However, environmental factors (Hunter and Donaldson, 1983;Devlin and Nagahama, 2002;Piferrer et al, 2012;Díaz and Piferrer, 2015) and hormonal manipulations may intensify this process (Piferrer, 2001;Lin et al, 2012;Alcántar-Vázquez et al, 2015;Marín-Ramírez et al, 2016;Juárez-Juárez et al, 2017). In this concern, the most conventional route of ovarian development involves the transcription of the Cyp 19a1a gene and the production of the enzyme aromatase complex (P450arom).…”
Section: Discussionmentioning
confidence: 99%
“…Although the duration of hormonal treatment has been pointed out as an important factor to successfully induce high rates of sex reversal, in recent years, both feminization and masculinization experiments with Nile tilapia, have shown that it is not necessary to administer the hormone for more than 20 days after the onset of the labile period to induce high rates of sex reversal [12,42,43,44]. Nakamura and coauthors [45] reports that under the light microscope, the first signs of gonadal sex differentiation appear in Nile tilapia fry at 23-26 days after hatching with the formation of the ovarian cavity in the XX gonad or the efferent duct in the XY gonad.…”
Section: Discussionmentioning
confidence: 99%
“…Vol.66: e23210792, 2023 www.scielo.br/babt in a general way, of the health status of the reared fish [58,59,60]. Values close to 2.0 have been reported for the Nile tilapia and its hybrids grown under optimal [12,54,59,60]. The CF can also be implemented to assess the physiological state of fish under potential stress [55], such as feeding Nile tilapia fry with a steroid enriched food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation